Transcriptional analysis of Myceliophthora thermophila on soluble starch and role of regulator AmyR on polysaccharide degradation. (October 2018) - Xu, Guanbao; Li, Jingen; Liu, Qian; Sun, Wenliang; Jiang, Min; Tian, Chaoguang
Highlights: The first transcriptomic analysis for thermophilic fungus M. thermophila on starch. Overexpression of Mycth_72393 and amyR significantly increased amylase activity. amyR disruption led to 3-fold increased lignocellulase activities on cellulose. Abstract: Thermophilic fungus Myceliophthora thermophila has great capacity for biomass degradation and is an attractive option for use as cell factory to produce chemicals directly from renewable polysaccharides, such as starch, rather than monomer glucose. To date, there has been no transcriptomic analysis of this thermophilic fungus on starch. This study determined the transcriptomic profile of M. thermophila responding to soluble starch and a 342-gene set was identified as a "starch regulon", including the major amylolytic enzyme (Mycth_72393). Its overexpression led to increased amylase activities on starch by 35%. Furthermore, overexpressing the key amylolytic enzyme regulator AmyR in M. thermophila significantly increased amylase activity by 30%. Deletion of amyR by the CRISPR/Cas9 system led to the relief of carbon catabolite repression and 3-fold increased lignocellulase activities on cellulose. This study will accelerate rational fungal strain engineering for biochemical production from biomass substrates such as raw corn starch and even crop straw.